Assessment of the project management system in the context of the implementation of large–scale projects: approaches and indicators - Nina Simionova; Radomir Simionov; Nikolay Sinyak (Недвижимость: экономика, управление, 2021)
A constant search for effective management tools becomes necessary against the background of economic globalization, growing competition, fast changing environmental factors, increasingly stringent product quality requirements. The project management methodology can boost management efficiency by focusing efforts on a specific area of activity and implementing the necessary strategic changes. As management problems become more complicated, the project management system itself undergoes changes and moves to a new level of organizational maturity, but the process of these changes cannot be considered complete. It is necessary to use performance indicators to boost the motivation of a project team.